The one and the many contemporary collaborative art in a global context - Kester, Grant H. (Duke University Press, 2011)
From text to action -- Park fiction, ala plastica, and dialogue -- The risk of diversity -- Programmatic multiplicity -- Art theory and the post-structuralist canon -- Lessons in futility -- Enclosure acts -- The twelfth seat and the mirrored ceiling -- The atelier as workshop -- Labor, praxis, and representation -- The divided and incomplete subject of yesterday -- Memories of development -- The limits of ethical capitalism -- The art of the locality -- Blindness and insight -- The invention of the public -- The boulevards of the inner city -- Park fiction : desire, resistance, and complicity -- A culture of needles : project row houses in Houston
Description based on print version record. - Includes bibliographical references and index
Keywords: Artistic collaboration; Creation (Literary, artistic, etc.); Art / Philosophy; Kunst; Ästhetik; Kooperation